(untitled) (Jurnal Teknologi Industri Pertanian, 2024)
Prill fat is a by-product of cooking oil production that can be utilized as a fat source in animal feed. The prill fat’s fine granular form and difficulty in achieving homogeneity with other materials pose challenges in its utilization. Processing prill fat into supplement wafers can be an alternative for its use, with careful consideration of its melting point. This study aims to optimize the production process of supplement wafers containing prill fat using response surface methodology (RSM) and to evaluate the changes in quality during storage. The research stages include optimizing the production process with temperature and heating time as factors, and the responses tested are production efficiency, moisture content (MC), and wafer durability index (WDI). The optimal temperature and heating time identified were 50°C for 1 minute, yielding a production efficiency of 95.2%, a moisture content of 5.6%, and a WDI of 95%, with the validation results showing a confidence level of 95%. It can be concluded that a temperature of 50°C with a heating time of 1 minute can be applied to produce supplement wafers containing prill fat. Keywords: production optimizing, prill fat, response surface methodology, wafer supplements